2009
DOI: 10.1002/j.2050-0416.2009.tb00359.x
|View full text |Cite
|
Sign up to set email alerts
|

The Influences of Steeping Duration and Temperature on the α- and β-Amylase Activities of Six Thai Rice Malt Cultivars (Oryza sativa L. Indica)

Abstract: A preliminary study of malting conditions for six Thai rice cultivars was conducted. Three non-glutinous rice cultivars (KDML105, PT60, and WR) and three glutinous rice cultivars (SPT, RD6, and KND) were selected. The steeping durations (24, 48, and 72 h) and temperatures (20, 25 and 30°C) were investigated for their effect on α-and β-amylase, the key enzymes for malt quality evaluation. During steeping, the production of both enzymes was lower than at the germination process. The longer the steeping duration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 22 publications
1
16
0
Order By: Relevance
“…Extract content of RRM and barley malt was 67.1% w/w and 78.1% w/w, respectively. The lower extract yield of RRM can be associated with insufficient enzymes activity (alpha and beta amylase) (Usansa et al ., 2009; Mayer et al ., 2014) to hydrolyse the complex starch matrix, which accounted for low solubility. In addition, temperature‐dependent starch hydrolysis (gelatinization and degradation) in congress mashing was not optimum for the rice starch hydrolysis, because rice cultivars have gelatinisation above 70 °C (Moirangthem et al ., 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Extract content of RRM and barley malt was 67.1% w/w and 78.1% w/w, respectively. The lower extract yield of RRM can be associated with insufficient enzymes activity (alpha and beta amylase) (Usansa et al ., 2009; Mayer et al ., 2014) to hydrolyse the complex starch matrix, which accounted for low solubility. In addition, temperature‐dependent starch hydrolysis (gelatinization and degradation) in congress mashing was not optimum for the rice starch hydrolysis, because rice cultivars have gelatinisation above 70 °C (Moirangthem et al ., 2020).…”
Section: Resultsmentioning
confidence: 99%
“…This short malting time was achieved at a higher germination temperature of 30°C and would most likely result in lower malting losses (in roots and coleoptile). Under similar conditions – steeping for 24 h and germinating at 30°C – six white Thai rice cultivars have been reported to result it average malting losses of 10, 20 and 40% for a total malting time of four, five and six days, respectively .…”
Section: Resultsmentioning
confidence: 99%
“…Usansa et al . reported that enzyme production during malting of rice was dependent on the rice variety and did not correlate with amylose content . There have been reports of successful brewing with 100% rice malt, made possible by optimising the mashing conditions , and of the experimental development of speciality rice malts, roasted to enhance the flavour and the colour .…”
Section: Introductionmentioning
confidence: 99%
“…Different milling methods in producing flour are thought to cause damage to starch and different chemical compositions. During soaking process, the hydrolisis of the constituent polymer become to component that has more solubility in the soaking media, so it can cause the chemical compositions of flour is changed (Usansa et al, 2009). In addition, mechanical process such as milling can also cause starch damage 5-14% (Dubat, 2004).…”
Section: The Effect Starch On Flour Qualitymentioning
confidence: 99%
“…This is caused by activated amylase enzyme on soaking process using wet milling method. It can hydrolize amylose into soluble dextrin (Usansa et al, 2009).…”
Section: Amylose Contentmentioning
confidence: 99%